A new species of Podanotum Torres & Johnson, 1996 (Lepidoptera, Lycaenidae) from northern Peru - Farfan, Jackie (2021)
We describe a new species of the genus Podanotum Torres & Johnson, 1996, Podanotum pajaten Farfán, Cerdeña & Bálint sp. nov. from northern Peru, associated with the Andean treeline ecotone adjacent to cloud forest and wet grassland at 3200 m above sea level. Description of this new species is based on one female adult and is distinguishable from its congeners by the combination of the following morphological characters: dorsal wing pale blue, forewing discoidal line present on ventral side, hindwing tailed, and ostium bursae distally toothed. Podanotum pajaten sp. nov. is separated geographically from the closest spatial species, P. glorissimum Bálint & Wojtusiak, 2002, by approximately 100 km to the south, and represents the second species described for Peru. An identification key to all known species of Podanotum is provided, stating their distributions by country. Publicación registrada en Zoobank/ZooBank article registered:LSIDurn:lsid:zoobank.org:pub:FE6C35CF-2609-410C-9CB5-57737D02DFC3Acto nomenclatural/nomenclatural act:Podanotum pajaten Farfán, Cerdeña & Bálint, 2021LSIDurn:lsid:zoobank.org:act:B8CE9125-0182-4DAB-BD92-D15DC4E16C47